2008
DOI: 10.1196/annals.1427.007
|View full text |Cite
|
Sign up to set email alerts
|

Brain Glucose Hypometabolism and Oxidative Stress in Preclinical Alzheimer's Disease

Abstract: One of the main features of Alzheimer's disease (AD) is the severe reduction of the cerebral metabolic rate for glucose (CMRglc). In vivo imaging using positron emission tomography with 2-[ 18 F] fluoro-2-deoxy-D-glucose (FDG-PET) demonstrates consistent and progressive CMRglc reductions in AD patients, the extent and topography of which correlate with symptom severity. Increasing evidence suggests that CMRglc reductions occur at the preclinical stages of AD. CMRglc reductions were observed on FDG-PET before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
341
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(364 citation statements)
references
References 106 publications
15
341
0
Order By: Relevance
“…While debate surrounds astrocytic metabolic supply and demand, it is clear that brain glucose metabolism is decreased in preclinical patients (96), animal models of dementia (97) and people with a diagnosis of AD (98). The molecular mechanisms behind this are poorly understood, although human AD studies highlight that astrocyte/endothelial GLUT1 (as well as neuronal GLUT3) levels are reduced in post-mortem AD brains (99,100).…”
Section: Slc2a Glucose Transportersmentioning
confidence: 99%
“…While debate surrounds astrocytic metabolic supply and demand, it is clear that brain glucose metabolism is decreased in preclinical patients (96), animal models of dementia (97) and people with a diagnosis of AD (98). The molecular mechanisms behind this are poorly understood, although human AD studies highlight that astrocyte/endothelial GLUT1 (as well as neuronal GLUT3) levels are reduced in post-mortem AD brains (99,100).…”
Section: Slc2a Glucose Transportersmentioning
confidence: 99%
“…Numerous functional imaging studies demonstrated significant and progressive decrease in glucose use from the very early stages of AD in humans. 192 The A␤ remodels astroglial metabolic phenotype in vitro by affecting glucose metabolism and increasing reactive oxygen species production in cultured astrocytes. The data on actual mechanisms of A␤-dependent changes in glucose metabolic pathways are controversial.…”
Section: Metabolic Remodeling Of Astroglia In Admentioning
confidence: 99%
“…The concept that AD could represent a metabolic disease stemmed from the findings that deficits in cerebral glucose utilization are detectable in the early stages of disease (Adolfsson, Bucht et al 1980;Fujisawa, Sasaki et al 1991;Caselli, Chen et al 2008;Mosconi, Pupi et al 2008;Mosconi, Mistur et al 2009;Langbaum, Chen et al 2010), and as AD progresses, so do the metabolic abnormalities (Hoyer and Nitsch 1989;Hoyer, Nitsch et al 1991). Although several studies provided initial clues that insulin resistance could be an important feature of AD (Frolich, Blum-Degen et al 1998;Hoyer 2002;), the human postmortem brain studies were critical for definitively establishing that both insulin resistance and insulin deficiency in the brain were consistent and fundamental abnormalities in AD (Rivera, Goldin et al 2005;Steen, Terry et al 2005).…”
Section: Brain Insulin and Insulin-like Growth Factor Problems In Admentioning
confidence: 99%